Single-cell RNA sequencing identifies a migratory keratinocyte subpopulation expressing THBS1 in epidermal wound healing - Ratklao Siriwach; Anh Quynh Ngo; Makio Higuchi; Kentaro Arima; Satoko Sakamoto; Akira Watanabe; Shuh Narumiya; Dean Thumkeo (iScience, 2022)
Summary: Keratinocyte differentiation is an intricate process that is regulated by multiple mediators. Using cultured human keratinocytes, we found that lysophosphatidic acid (LPA) induced the differentiation of a previously unsuspected keratinocyte subpopulation expressing the extracellular matrix protein, thrombospondin-1 (THBS1). This action of LPA was mediated by the RHO/ROCK-SRF signaling downstream of LPA1 and LPA5 receptors and required ERK activity. Suppression of THBS1 in vitro suggested a migratory role of THBS1+ keratinocytes. Moreover, we analyzed publicly deposited single-cell RNA sequencing dataset and identified Thbs1-expressing keratinocytes in the mouse wound skin. Immunohistochemistry analysis revealed that Thbs1+ keratinocytes were apparently differentiated from basal keratinocytes upon wounding, subsequently polarized and migrated suprabasally toward the wound front, and eventually underwent terminal differentiation in the neo-epidermis. Importantly, inhibition of Erk activity suppressed Thbs1+ keratinocyte differentiation in wound healing. Based on these findings, we suggest that THBS1+ keratinocyte is a migratory keratinocyte subpopulation that facilitates epidermal wound healing.